Approaching energy-dense and cost-effective lithium–sulfur batteries: From materials chemistry and price considerations. (15th June 2020) - Yang, Chen; Li, Peng; Yu, Jia; Zhao, Li-Da; Kong, Long
Abstract: Lithium–sulfur (Li–S) batteries are one of promising candidates for the emerging applications that demand of high-energy and low-cost power sources. The pouch cell configuration is an essential platform to truly evaluate the advantages, challenges and opportunities of Li–S batteries. Herein, a critical link of specific energy and cost to pouch cell parameters is established to figure out importance of individual components in cells and hopefully direct future meaningful investigations. The specific energy analysis of a pouch cell indicates that realizing a projected specific energy of more than 500 Wh kg −1 requires to push critical cell parameters to their limits and that the electrolyte volume dominantly determines specific energy and cost of a Li–S pouch cell. Therefore, low-cost and high-energy Li–S batteries principally relies on stable operations of batteries under electrolyte-lean conditions. Especially, the cost of lithium salts used in Li–S batteries has a large room to fall down, by which Li–S batteries are expected to be more sustainable and affordable in the emerging applications. This Perspective article affords an alternative view to call for practical approaches to promote Li–S batteries toward markets. Graphical abstract: Image 1 Highlights: Li–S batteries are quantitatively analyzed based on pouch cell configurations. A link of specific energy and cost to pouch cell parameters is established. Electrolytes take a large portion of weight and cost in a pouch cell. Achieving a 500 Wh kg −1 in cells pushes cell parameters to their limits. Low cost lithium salts promise an affordable Li–S batteries.